Equality and the Notwithstanding Clause : Considering the Nature and Application of Section 28 of the Canadian Charter - Hartery, Jesse (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2023)
This article considers the nature and application of section 28 of the Canadian Charter of Rights and Freedoms. I begin by describing the two major camps in the scholarship, i.e., those who see section 28 as an interpretative and non-absolute provision with no substantive content and those who see it as an independent and/or absolute substantive provision that effectively blocks the effect of section 33 when it is invoked. While the second camp provides a compelling textual and historical account of the provision, I seek to show that there is a middle ground between these positions, one that recognizes the substantive nature of section 28, while clearly identifying its nature as an autonomous guarantee with a more limited application with respect to the provisions targeted by section 33. I argue that section 28 must be tied to a guaranteed right or freedom and, therefore, that there is a strong argument to make that it is of no use when the underlying supra-legislative provision on which it must rely is limited or inapplicable. However, this would not affect its autonomous substantive function in contexts in which section 33 is not or cannot be invoked.